2020
DOI: 10.1021/acsaem.0c01391
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Properties of Benzothiadiazole Dyes for Efficient Visible Light-Driven Photocatalytic H2 Production under Different Conditions

Abstract: Photocatalytic hydrogen production has recently emerged as a promising process for the long-term storage of solar energy. In this work, we studied the application of a series of heterogeneous photocatalysts obtained by sensitizing Pt/TiO2 nanoparticles with 10 different D-π-A organic dyes containing the benzo­[c]­[1,2,5]­thiadiazole (BTD) heterocyclic moiety in H2 generation. Starting from the known DSSC sensitizer RK-1, our approach involved the systematic and simultaneous alteration of several important stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…On the contrary, the rate per unit surface area is associated with the electronic transfer dynamics of the photocatalyst, although it is unable to eliminate all of the uncertain factors for the real photocatalysis . Herein, it is encouraged to compare the photocatalytic reaction rates both per unit weight and per unit surface area of the photocatalyst, which is considered as a more favorable approach for expressing the photocatalytic activity. , From Figure c, it is observed that the order of photocatalytic H 2 evolution rate per surface area is as follows: 3% Pt 1 @TpPa-1 > 5% Pt 1 @TpPa-1 > 3% Pt NPs/TpPa-1 > 1% Pt 1 @TpPa-1 > TpPa-1, which is consistent with the order of photocatalytic H 2 evolution rate per unit mass, and the corresponding overall H 2 production (μmol m –2 ) after 6 h of irradiation is presented in Table . It shows that the 3% Pt 1 @TpPa-1 exhibits the highest photocatalytic H 2 evolution performance per unit surface area (17.24 μmol m –2 ), which is almost 3 and 66 times that of 3% Pt NPs/TpPa-1 (5.64 μmol m –2 ) and bare TpPa-1 (0.26 μmol m –2 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the rate per unit surface area is associated with the electronic transfer dynamics of the photocatalyst, although it is unable to eliminate all of the uncertain factors for the real photocatalysis . Herein, it is encouraged to compare the photocatalytic reaction rates both per unit weight and per unit surface area of the photocatalyst, which is considered as a more favorable approach for expressing the photocatalytic activity. , From Figure c, it is observed that the order of photocatalytic H 2 evolution rate per surface area is as follows: 3% Pt 1 @TpPa-1 > 5% Pt 1 @TpPa-1 > 3% Pt NPs/TpPa-1 > 1% Pt 1 @TpPa-1 > TpPa-1, which is consistent with the order of photocatalytic H 2 evolution rate per unit mass, and the corresponding overall H 2 production (μmol m –2 ) after 6 h of irradiation is presented in Table . It shows that the 3% Pt 1 @TpPa-1 exhibits the highest photocatalytic H 2 evolution performance per unit surface area (17.24 μmol m –2 ), which is almost 3 and 66 times that of 3% Pt NPs/TpPa-1 (5.64 μmol m –2 ) and bare TpPa-1 (0.26 μmol m –2 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The number of incident photons in unit time (h –1 ) was calculated using eq Thus, AQE ( i.e ., the apparent quantum yield (AQY)) was calculated using eq , Turnover number (TON) was calculated from the overall amount of H 2 evolved in 6 h during the photocatalytic reaction according to eq ,, Turnover frequency (TOF) is a kinetic-dependent parameter, which was calculated according to eq , …”
Section: Experimental Sectionmentioning
confidence: 99%
“…We have also synthesized the reference chromophores of the dyads, namely, BODIPY ( BDP ), (Zn)­Porphyrin ( Por ), and BDP­(Im) . Overall, BDP-Por and BDP­(Im)-Por reached 17 500 and 13 700 TONs (vs PS), respectively, whereas BDP-Por-BDP­(Im) (18 600 TONs) exhibited a record high H 2 production of 225 mmol­(H 2 ) g­(cat) −1 h –1 with respect to similar noble-metal-free photosensitizers in the literature. , …”
Section: Introductionmentioning
confidence: 73%
“…The substituent (or substituents) in this sense plays an essential role in the final hydrophobic or hydrophilic character of the ultimate small organic fluorophore; therefore, having a direct effect on the cellular localization or on other biological applications of the BTD dye. The hydrophobic feature of the BTD core is commonly improved by π‐extension (e. g. Ph, C=C or C≡C groups) in the 4,7‐ positions of the structure [54] . It is not rare to see the BTD core described as a hydrophobic structure.…”
Section: Featured Physicochemical Properties Of Btd Derivativesmentioning
confidence: 99%